Is a CT Scan Needed for Pedicle Screws Crossing the Midline? Quality Improvement Case Series - Williams, Jestin; Peter D’Amore; Manaf Younis; King, Andrew; Carter Clement (Journal of the Pediatric Orthopaedic Society of North America, 2021)
Posterior spinal fusion (PSF) is an effective and safe treatment for various spinal deformities in the pediatric population, including Scheuermann’s Kyphosis. Several studies have evaluated the variations in pedicle anatomy, parameters to detect pedicle breach, and need for postoperative computerized tomography scan (CT scan). The purpose of this case study is to present an example of PSF in a relatively large male patient with Scheuermann’s Kyphosis. The surgery was uneventful and relatively long pedicle screws were used. Postoperative X Rays showed pedicle screws crossing the midline at several levels. Further work up with CT did not demonstrate any medial breaches. In conclusion, long pedicle screws are not necessarily malpositioned if they cross the midline.